2017
DOI: 10.3389/fphar.2017.00591
|View full text |Cite
|
Sign up to set email alerts
|

Technical Improvement and Application of Hydrodynamic Gene Delivery in Study of Liver Diseases

Abstract: Development of an safe and efficient in vivo gene delivery method is indispensable for molecular biology research and the progress in the following gene therapy. Over the past few years, hydrodynamic gene delivery (HGD) with naked DNA has drawn increasing interest in both research and potential clinic applications due to its high efficiency and low risk in triggering immune responses and carcinogenesis in comparison to viral vectors. This method, involving intravenous injection (i.v.) of massive DNA in a short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 131 publications
(125 reference statements)
2
14
0
Order By: Relevance
“…HGD is widely accepted as an efficient method that enables the in vivo transfer of NAs into mouse hepatocytes via the caudal vein [42,43]. Gene delivery to the kidneys and lungs is also possible with this method, although the transfection efficiency is low and the number of transferred NAs appears to be low, in the case of a successful transfection [9].…”
Section: Discussionmentioning
confidence: 99%
“…HGD is widely accepted as an efficient method that enables the in vivo transfer of NAs into mouse hepatocytes via the caudal vein [42,43]. Gene delivery to the kidneys and lungs is also possible with this method, although the transfection efficiency is low and the number of transferred NAs appears to be low, in the case of a successful transfection [9].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain this, we employed the PB system, which allows chromosomal integration of an exogenous DNA of approximately 10 kb in size [ 20 ]. It has been reported that the expression of a chromosomally integrated GOI via the PB system continued over 300 days [ 33 ], and that HGD-mediated gene delivery of a naked plasmid in the liver confers the GOI an expression lasting for approximately 4 weeks [ 2 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results remain inferior compared with those achieved using genome integration via viral vectors. This problem, the gene transfer efficiency of nonviral vectors, has been further addressed by the development of devices that allow for continuous injection of DNA deep into the body, such as into the liver [ 49 , 50 ]. Although these devices are clearly useful, typically, the treatment of genetic deficiencies must continue throughout life, such that nonviral delivery might never be as convenient or effective as viral-mediated integration of DNA into the genome.…”
Section: Efficiency Of Gene Therapy With Nonviral Vectorsmentioning
confidence: 99%